ЕЛЕКТРОТЕПЛОВІ ПРОЦЕСИ ІНДУКЦІЙНОЇ ОБРОБКИ СЕГМЕНТОВАНОЇ ЖИЛИ СИЛОВОГО КАБЕЛЮ (ДОСЛІДЖЕННЯ З ЕЛЕМЕНТАМИ БАГАТОМАСШТАБНОГО МОДЕЛЮВАННЯ) - Кучерява , І.М. (Інститут електродинаміки НАН України, Київ, 2024)
The article presents the study of electromagnetic-thermal processes during the induction treatment of cable segmented (Milliken) conductor moving in the alternating magnetic field of cylindrical inductor. The study is carried out at two scale levels: at the scale of the entire conductor and inductor (by numerical solution of two-dimensional electromagnetic problem) and at the scale of separate segment of the conductor as its basic (representative) element (the three-dimensional thermal problem is successively solved with the use of electromagnetic results). The characteristic properties of the distributions of current density, Joule losses and temperature in the cross-section and along the moving conductor are analyzed. The special features of conductor heating during the treatment and the conditions for reaching the required temperature are determined. References 19, figures 6.